LANGUAGE LEARNING STYLE PREFERENCES OF SUCCESSFUL EFL LEARNERS OF BANGLADESH - Tania Tahmina (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2022)
A learner’s learning style is a complex paradigm. This study was conducted to explore the most dominant language learning style of the successful learners of the Department of English, Jagannath University, Dhaka, Bangladesh. The study used a mixed method. The data was obtained from a questionnaire, learners’ scores, and interviews. Twenty learners were classified as high achievers who participated in this study. This study used a 24-item Barsch Learning Style Inventory (BLSI) as a research instrument and measured learners’ learning styles through short answer questions and categorized them as visual, auditory, or kinesthetic. The learners’ academic achievement was determined by their Grade Point Average (GPA) of the last term-final examination. Five learners were selected for the semi-structured in-depth interviews. The findings indicate that the dominant learning style of the high achiever learners was visual learning style preferences, with a mean score of 63.75. The results of the study will contribute to the current understanding of good language learners’ preferences of learning styles and provide insight for learners, teachers, curriculum designers, administration, and future researchers.